Non-silicate iron in mineral-associated organic matter of agro-chernozems located on different positions on the slope - E. V. Tsomaeva; Z. S. Artemyeva; E. S. Zasukhina; E. B. Varlamov (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
Data on total non-silicate iron (Fed) content in mineral-associated organic matter (MAOM) of agro-chernozems of different localization on the slope are presented. The distribution of total non-silicate iron in soil profile follows that of organic carbon (OC): the maximum values are confined to the surface horizons, and decrease down the profile. It has been revealed that the change in the content of non-silicate iron in the MAOM of the clay fraction in arable horizons of eroded agro-chernozems is a result of erosion processes, including their intensity, which also depends, among other things, on the slope steepness. A lower slope steepness (4°) contributes to an increase in the organic carbon loading on iron oxides, resulting in an increased in iron desorption capacity, while a higher slope steepness (6°) results in lower iron desorption capacity. The OC/Fed molar ratio is suggested as an additional indicator of the degree of soil erosion. In clay fractions, of both their position in the soil profile and their position on the slope, the predominant mechanism of organic matter stabilization was the formation of organic-iron complexes (OC/Fed > 10). In the Residue fraction of humus horizons, non-silicate iron seems to be presented mainly as iron carbonates (FeCO3), while the proportion of microaggregates (stable under the sonication), where OM is mainly humin, is relatively low against the background of the absolute dominance of primary minerals in this fraction (weight %). Most of the non-silicate iron of mineralassociated OM extracted by dithionite-citrate-hydrocarbonate is localized in the clay fraction – 2/3 or more.